PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI PADA BADAN PENGAWAS PEMILIHAN UMUM PROVINSI SULAWESI TENGGARA - Marlina Marlina; Yusuf Montundu; Sinarwaty Sinarwaty; Riski Amalia Madi (Pascasarjana Universitas Halu Oleo, 2022)
This study was conducted with the aim of analyzing and knowing the partial effect of transformational leadership style on employee performance, work motivation on employee performance, and organizational commitment on employee performance, as well as simultaneously testing the effect of transformational leadership style, work motivation, and organizational commitment on employee performance. This research was conducted at General Election Supervisory Board of Southeast Sulawesi Province by taking samples of Civil Servants with a total of 83 people in Regencies and Cities in Southeast Sulawesi Province. This research approach is quantitative research with data collection method using questionnaires and the collected data is processed using multiple linear regression. Based on the results of this study, it was found that partially transformational leadership style has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Simultaneously it was found that transformational leadership style, work motivation and organizational commitment have a positive and significant effect on employee performance. From the tests conducted, it was found that organizational commitment has the largest coefficient in influencing changes in employee performance.